XUV‐induced transient phase gratings for probing ultra‐fast carrier generation and recombination processes in wide‐bandgap semiconductors. Issue 1 (10th December 2012) - Gabrysch, Markus; Schwenke, Jörg; Balciunas, Tadas; He, Xinkui; Rakowski, Rafal; Johnsson, Per; Canton, Sophie E.; Isberg, Jan; L'Huillier, Anne; Hommelhoff, Peter; Kling, Matthias; Stockman, Mark
<x xml:space="preserve">Abstract</x> A method for probing the temporal evolution of ultra‐fast carrier generation and recombination processes in wide‐bandgap semiconductors, e.g. diamond, is described. Two extreme ultraviolet (pump) pulses produced by high‐order harmonic generation in Argon gas (with a photon energy of 32 eV) are superimposed on a sample with a small angle between them, inducing periodic changes in the refractive index of the material causing it to act as a transient diffraction grating. A delayed synchronized infrared (probe) pulse gets diffracted on the induced phase grating and is detected in the first diffraction order. By varying the time‐delay between pump and probe, the full temporal evolution of the free carrier generation and recombination processes can be resolved. Feasibility calculations and the first steps towards experimental implementation are presented.